Microscopic Image of Calcium Oxalate Crystals in the Urine of Residents Who Consume Boiled Dug Well Water in Dampang Village, Bulukumba Regency - Megawati , Rizki; Artati, Artati; Salnus , Subakir (CV. Science Tech Group, 2024)
Crystals are formed about the concentration of various salts in the urine related to the patient's food metabolism and fluid intake and the impact of changes that occur in the urine after sample collection (i.e. changes in pH and temperature that change the solubility of salts in the urine and result in crystal formation). Calcium oxalate crystals are most commonly found in acidic and neutral urine. The most common form is the dihydrate form, colored crystals that resemble an envelope. This type of crystal is found in normal urine, especially after consuming large doses of ascorbic acid or foods rich in oxalic acid. This study used a descriptive research design. Urine sediment examination is one type of routine urine examination that uses a microscopic method using a microscope instrument. The results obtained from 36 urine samples of dug well water consumption showed 5 samples (13.9%) positive for calcium oxalate crystals, while 31 samples (86.15%) were negative for calcium oxalate. Based on the results of the study, it showed the presence of calcium oxalate crystals in the urine of residents who consumed boiled dug well water in Dampang Village, Bulukumba Regency.